P->P2O5->H3PO4->Na3PO4->Ca3(PO4)2->H3PO4->Zn3(PO4)2
А)
1)4P + 5O2 = 2P2O5
2)P2O5 + 3H2O = 2H3PO4
3)H3PO4 + 3NaOH = Na3PO4 + 3H2O
4)2Na3PO4+ 3CaCl2=Ca3(PO4)2+ 2Na3Cl35)Ca3(PO4)2 +6H2O = 2H3PO4 + 3Ca(OH)2
6)2H3PO4 +3Zn= Zn3(PO4)2 + 3H2
б)
1)2P+Ca=Ca3P2
2)Ca3P2+6H2O=3Ca(OH)2+2PH3
3)2PH3+4O2=P2O5+3H2O
4)P2O5+3H2O=2H3PO4
5)3NaOH+H3PO4=Na3PO4+3H2O
6)Na3PO4+3AgNO3=3NaNO3+Ag3PO4
в)
Ca3(PO4)2+5 C+3 SiO2= 2P+3 CaSiO3+5 CO
2)4 P+5 O2 = 2 P2O53)P2O5+3 H2O = 2 H3PO4
4)H3PO4 + 3KOH -> K3PO4 + 3H2O
5)2K3PO4 + 3Fe(NO3)2 -> Fe3(PO4)2 + 6KNO3
P->P2O5->H3PO4->Na3PO4->Ca3(PO4)2->H3PO4->Zn3(PO4)2
А)
1)4P + 5O2 = 2P2O5
2)P2O5 + 3H2O = 2H3PO4
3)H3PO4 + 3NaOH = Na3PO4 + 3H2O
4)2Na3PO4+ 3CaCl2=Ca3(PO4)2+ 2Na3Cl3
5)Ca3(PO4)2 +6H2O = 2H3PO4 + 3Ca(OH)2
6)2H3PO4 +3Zn= Zn3(PO4)2 + 3H2
б)
1)2P+Ca=Ca3P2
2)Ca3P2+6H2O=3Ca(OH)2+2PH3
3)2PH3+4O2=P2O5+3H2O
4)P2O5+3H2O=2H3PO4
5)3NaOH+H3PO4=Na3PO4+3H2O
6)Na3PO4+3AgNO3=3NaNO3+Ag3PO4
в)
Ca3(PO4)2+5 C+3 SiO2= 2P+3 CaSiO3+5 CO
2)4 P+5 O2 = 2 P2O5
3)P2O5+3 H2O = 2 H3PO4
4)H3PO4 + 3KOH -> K3PO4 + 3H2O
5)2K3PO4 + 3Fe(NO3)2 -> Fe3(PO4)2 + 6KNO3